Triboelectric based high-efficiency filter device for engineering polluted hydraulic oil. (September 2022) - Qu, Zhaoqi; Cao, Jie; Shan, Chang; Zhang, Zhongqiang; Cheng, Guanggui; Ding, Jianning
Abstract: As an important part of hydraulic system, hydraulic oil pollution will seriously affect the service life of the system. Therefore, the pollution control of hydraulic oil is crucial to the normal operation of the hydraulic system. A high-efficiency filtration device for engineering polluted hydraulic oil based on triboelectric-coagulation is designed. Different from traditional agglomeration filtration methods such as high-voltage static electricity and external magnetic fields, this work uses the triboelectric effect to charge and agglomerate hydraulic oil particles, and then filters them. The equipment cost is low and the filtration method is green and pollution-free. The theoretical analysis and finite element simulation results proves the feasibility of this filter device. The experimental pipeline was designed and built, and the filtration performance of the polluted hydraulic oil was carried out. The experimental results show that the device has a good interception effect on the solid particles of the polluted hydraulic oil, and the removal rate reaches 99%. This device has strong practicability and broad application prospects, and it is of great significance to purify contaminated hydraulic oil. Highlights: Triboelectric based high-efficiency filter device for engineering polluted hydraulic oil was designed. The removal rate of the filter device reaches 99%. The theoretical analysis and experiments on the filter device are carried out.